Practical Method for Estimating Seismic Risks of a Wooden House at an Arbitrary Point - ICASP14; Mizutani, Yukari; Mori, Yasuhiro; Sugai, Michiyo (My University, 2023)
The aim of this paper is to report the results of assessment of seismic risks of a wooden house using natural period-dependent spectrum intensity (SIIg) and probabilistic damage index function. SIIg is defined as the integral of the velocity response spectrum. The velocity response spectrum are approximated, in this paper, by the transformation of a power spectrum density function estimated from an acceleration Fourier amplitude spectrum (AFS). The major findings of this analysis are outlined below. 1) The AFS on the ground surface at one of seismometer points in Owari-asahi City was estimated using the transfer functions and the observed records at the other seismometer points. By using observed records in the city and Kik-net installed outside the city, the estimation accuracy of AFS all seismometer points are particularly higher than using only observed records in the city. 2) The seismic risks estimated by AFS calculated using data of Kik-net are much better correspond to those by observed AFS than those by AFS calculated using data only in the City. However, the risks by AFS using Kik-net are still not quite identical to those by the observed AFS. It became clear that little variation of AFS dose affect the estimations of seismic risks, and the accuracy of calculating AFS should be taken into account for the risk estimations.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED